PENGARUH PARTISIPASI PUBLIK, AKUNTABILITAS, TRANSPARANSI DAN INTEGRITAS TERHADAP KINERJA KEUANGAN KABUPATEN BENGKULU TENGAH - Suryani, Pesi (JURNAL FAIRNESS, 2019)
This study aims to examine the influence of public participation, accountability, transparency and integrity to the regional financial performance of Central Bengkulu District. Populations in this study are all financial managers that exist in the organization of regional government of Central Bengkulu District, where there are 38 organizations of regional devices. While the sample in this study is based on purposive judgement sampling method, where researchers have determined some previous criteria.The result of this research showed that public participation, accountability and integrity have a positive effect on the regional financial performance of Central Bengkulu District. While transparency hasn’t effect on the regional financial performance of Central Bengkulu District.That findings imply that the district government of Central Bengkulu should be maintained and improved the level of public participation, accountability, transparency and integrity of local financial management in order to improve its financial performance.